The Historical Novel, Scottish Nationalism and the Good Hero: Jane Porter’s The Scottish Chiefs as Historiography - Bies, John (Advances in Social Sciences Research Journal, 2021)
This study analyses the relationship between the historical novel and historiography within the context of the historical evolution of Scottish nationalism as impacted by the image of the good hero. Specifically, it illustrates how Jane Porter used the myth of William Wallace to tap into the concept of the Scottish nationhood and how the country views its hero via her historical novel The Scottish Chiefs. By analysing her writings, it is argued that the genre of historical fiction can be used by historical researchers as source material from a historiographical point of view to understand how her early nineteenth century novel can be used to understand the concept of Scottish nationhood as viewed in that country during the eighteenth and nineteenth centuries. Though Jane Porter is often described as a minor author, she played a significant role in using the historical novel to promote a heroic Scottish identity. By examining The Scottish Chiefs through historiographic lenses, it was possible to conjecture it’s contribution to Scotland’s perceptions of its historical heroes and fight for independence. What made Porter different from other novelists, such as Sir Walter Scott and Robert Burns was the fact that she imagines the behaviour of an actual historical figure during the First War of Scottish Independence between 1296 and 1328.